Optimization of the Indonesian Ombudsman in resolving reports on public service maladministration - Maiyestati Maiyestati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the role of the Ombudsman of the Republic of Indonesia Representative of West Sumatra in resolving reports of public service maladministration and identifies the obstacles and improvement efforts undertaken. Using a sociological legal research approach, the study is based on primary data obtained through semi-structured interviews and field observations, as well as secondary data from laws, regulations, and relevant documents. The findings indicate that the Ombudsman plays a significant role in handling maladministration cases; however, its performance has not yet been optimal due to limitations in human resources, operational budget, infrastructure, report complexity, and resistance from reported institutions. To address these challenges, the Ombudsman has implemented several strategies, including task optimization, digitalization of report management, public reporting education, inter-agency coordination, and budget advocacy. These efforts contribute positively to improving the effectiveness of complaint handling and strengthening public service accountability and citizen rights protection at the regional level.